Constraint Propagation in Propositional Planning - Sideris, Andreas; Dimopoulos, Yannis (Proceedings of the International Conference on Automated Planning and Scheduling, 2010)
Planning as Satisfiability is a most successful approach to optimal propositional planning. It draws its strength from the efficiency of state-of-the-art propositional satisfiability solvers, combined with the utilization of constraints that are inferred from the problem planning graph. One of the recent improvements of the framework is the addition of long-distance mutual exclusion (londex) constraints that relate facts and actions which refer to different time steps. In this paper we compare different encodings of planning as satisfiability wrt the constraint propagation they achieve in a modern SAT solver. This analysis explains some of the differences observed in the performance of different encodings, and leads to some interesting conclusions. For instance, the Blackbox encoding achieves more propagation than the one of Satplan06, and therefore is a stronger formulation of planning as satisfiability. Moreover, our investigation suggests a new more compact and stronger model for the problem. We prove that in this new formulation many of the londex constraints are redundant in the sense that they do not add anything to the constraint propagation achieved by the model. Experimental results suggest that the theoretical results obtained are practically relevant.